Assessment of Respiration-Induced Motion and Its Impact on Treatment Outcome for Lung Cancer. (4th June 2013) - Wang, Yan; Bao, Yong; Zhang, Li; Fan, Wei; He, Han; Sun, Zong-Wen; Hu, Xiao; Huang, Shao-Min; Chen, Ming; Deng, Xiao-Wu
Abstract : This study presented the analysis of free-breathing lung tumor motion characteristics using GE 4DCT and Varian RPM systems. Tumor respiratory movement was found to be associated with GTV size, the superior-inferior tumor location in the lung, and the attachment degree to rigid structure (e.g., chest wall, vertebrae, or mediastinum), with tumor location being the most important factor among the other two. Improved outcomes in survival and local control of 43 lung cancer patients were also reported. Consideration of respiration-induced motion based on 4DCT for lung cancer yields individualized margin and more accurate and safe target coverage and thus can potentially improve treatment outcome.